Pressurised Fuel Vessel Mass Estimation for High-Altitude PEM Unmanned Aircraft Systems - Ibrahim M. Albayati; Abdulrahman Muataz Al-Bayati; Rashid Ali (Fuels)
The power to weight ratio of power plants is an important consideration, especially in the design of Unmanned Aircraft System (UAS). In this paper, a UAS with an MTOW of 35.3 kg, equipped with a fuel cell as a prime power supply to provide electrical power to the propulsion system, is considered. A pressure vessel design that can estimate and determine the total size and weight of the combined power plant of a fuel cell stack with hydrogen and air/oxygen vessels and the propulsion system of the UAS for high-altitude operation is proposed. Two scenarios are adopted to determine the size and weight of the pressure vessels required to supply oxygen to the fuel cell stack. Different types of stainless-steel materials are used in the design of the pressure vessel in order to find an appropriate material that provides low size and weight advantages. Also, the design of a hydrogen pressure vessel and mass estimation are also considered. The estimated sizes and weights of the hydrogen and oxygen vessels of the power plant and propulsion system in this research offer a maximum of four hours of flying time for the UAS mission; this is based on a Horizon (H-1000) Proton Exchange Membrane (PEM) stack.